Digital Marketing Implementation for Cosmetic Business Growth at Daily Aesthetic: Implementasi Pemasaran Digital untuk Pengembangan Usaha Produk Kosmetik Daily Aesthetic - arya bintang ilahi ilahi; Yulianto Mochamad Rizal (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Rapid technological advancements and globalization have transformed modern lifestyles, rendering digital connectivity essential for contemporary business operations. Specific Background: Within the highly competitive cosmetics industry, Daily Aesthetic utilizes digital platforms to build brand awareness and foster consumer interaction. Knowledge Gap: Despite the adoption of social media and e-commerce, businesses often struggle to maximize the utility of available platform features to drive growth. Aims: This study evaluates the digital marketing strategies employed by Daily Aesthetic and identifies the obstacles hindering the full utilization of digital platform potential. Results: The findings reveal that while the brand effectively uses Instagram and TikTok, it lacks optimal integration of critical features, such as TikTok’s shopping basket and Instagram’s pinning functionality, which limits purchase facilitation and content visibility. Novelty: This research provides an operational assessment by linking suboptimal feature utilization to restricted brand engagement and provides a technical roadmap for feature optimization. Implications: Cosmetic enterprises are advised to conduct rigorous audits of their digital platform features, specifically integrating direct purchasing tools and pinned content strategies, to improve the consumer journey and support sustainable business expansion. Highlights: Suboptimal utilization of e-commerce features on social platforms restricts purchase conversion rates. Inconsistent content visibility on visual-based social media hinders effective brand positioning. Direct integration of in-app shopping tools is essential for streamlining the consumer acquisition process. Keywords: Digital Marketing, Cosmetic Business, Marketing Strategy, Feature Enhancement, Online Sales